NMR and NQR investigation of the lattice dynamics in (CH₃)₂CHNH₃CdBr₃ - Chesnokov, Eu.D.; Chapla, Z.; Ovcharenko, A.I.; Pogrebnyak, S.V.; Vertegel, I.G. (Functional Materials, 2005)
The temperatures dependences of the Br⁷⁹ quadrupole resonance, Br⁷⁹ and proton spinlattice relaxation times have been studied in the perovskite layer structure compounds (CH₃)₂CHNH₃CdBr₃. It is shown that anomalies in the temperature behaviours of NQR frequencies and quadrupole relaxation of Br⁷⁹ and related to the reorientation of NH₃ groups. The main mechanisms of Br⁷⁹ and proton spin relaxation as well as their correlations with motion nature of the methylammonium groups and their fragments are discussed.